Multi-level Governance and Energy Specifics of the V4 Countries within the Context of European Integration - Bauerová, Helena; Vošta, Milan (Politics in Central Europe (Pilsen), 2020)
The topic of energy is still one of the most sensitive policy areas. The aim of this article is to examine the multi-level governance and energy specifics of the V4 countries within the context of European integration by analyzing selected the specifics of the energy mix of the V4 group countries. This will be carried out within the context of applying the theory of multilevel governance. The paper shows how energy policy is formed at state, and/or non-state level, as well as how these levels are influenced by the EU. The article also looks at the efforts taken to shape a common energy policy. A closer examination of the individual countries‘ levels lies outside the scope of this article. Therefore, the framework was chosen with regard to the particular features within the context of the functioning of the V4 group of countries. Using multi-level governance as a theoretical concept, the authors considered the limits arising from the determination of levels and the subjects of the survey, as well as having distinguished three levels of analysis. The first is the supranational level. This is represented by the EU. The second level is represented by the V4 states. The third level is the state as the actor that formulates energy policy, sets the energy mix and subsequently manifests itself in relation to the EU and the V4 group. Energy policy is significantly influenced by states, especially in the area of energy security of fuel supplies, or that of setting the energy mix. With the gradual communitarization of energy policy, the EU’s influence is growing and it is debatable how the evaluation of existing strategic plans, presented by individual states, will be done. The role of the V4 group is the weakest of the three levels of analysis which were examined. However, its increasing influence can be predicted mainly in the case of coal depletion and the perception of nuclear energy as a renewable source.